Short repeats in the spa gene of Staphylococcus aureus are prone to nonsense mutations: stop codons can be found in strains isolated from patients with generalized infection - Khrustalev, Vladislav Victorovich; Ghaznavi Rad, Ehsanollah; Neela, Vasantha Kumari; Shamsudin, Mariana Nor; Amouzandeh-Nobaveh, Alireza; Barkovsky, Eugene Victorovich (Elsevier, 2013)
Fifteen sequences with stop codons have been obtained in the course of standard methicillin-resistant Staphylococcus aureus (MRSA) spa typing. In nine of those sequences, stop codons occurred due to nonsense G-T and A-T transversions. G-T transversions would appear to be frequent in the spa gene, mostly due to symmetric mutational AT-pressure in the whole S. aureus genome and due to replication-associated mutational pressure characteristic of lagging strands of the "chromosome". A-T transversions would appear to be frequent in the spa gene mostly due to transcription-associated mutational pressure. Relative to other S. aureus genes, short repeats in spa are enriched by nonsense sites for G-T and A-T transversions; the probability of being nonsense for A-T transversion is high in that part of spa coding region. 13 out of 15 (87%) of the sequences with stop codons were obtained from strains isolated from patients with generalized S. aureus infection. Truncation of spa at its C-terminus is predicted to result in a protein that possesses functional IgG binding domains unable to be linked to the cell wall. This is discussed in light of the known fact that extracellular spa is a strong virulence factor involved in immune evasion.